Pengaruh Orientasi Belanja, Kepercayaan Online, Dan Kemudahan Terhadap Minat Beli Secara Online Di Tokopedia (Studi Kasus Pada Mahasiswa STIE Muhammadiyah Cilacap) - Rohman, Faizun Nur; Zamroni (JURNAL EKONOMI, 2021)
This study aims to : Effect of Shopping Orientation, Online Trust and Ease of Buying Interest Online at Tokopedia (A Case Study : STIE Muhammadiyah Cilacap Student).. The aim of this research is to analyze the efect of Shopping Orientation (X1), Online Trust (X2) and Ease (X3) of Buying Interest Online (Y) at Tokopedia (A Case Study: STIE Muhammadiyah Cilacap Student). The samples for the research are 70 student respondents at STIE Muhammadiyah Cilacap. The results showed that in the T test conducted partially, the variable online trust and ease affect buying interest while shopping orientation does not affect buying interest. This is indicated by tcount value of online trust 3,452, the ease of 4,708 is greater than the ttable 1,66691, while the value of the shopping orientation tcount is 0,195 smaller than the ttable 1,66691.Based on the results of the F regression test conducted it was found that all variables that influence shopping orientation, online trust dan easa simultaneously affect buying interest, this is indicated by the F test value which results in a Fcount value of 37,534 greater than Ftable 2,73. Keyword : Shopping Orientation, Online Trust, Ease, Buying Interest.